1998
DOI: 10.1021/ie9704455
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Recovery of Carbon Dioxide from Flue Gases of Coal-Fired Power Plants by Cyclic Fixed-Bed Operations over K2CO3-on-Carbon

Abstract: An efficient chemical absorption method capable of cyclic fixed-bed operations under moist conditions for the recovery of carbon dioxide from flue gases has been proposed employing K2CO3-on-carbon. Carbon dioxide was chemically absorbed by the reaction K2CO3 + CO2 + H2O ⇄ 2KHCO3 to form potassium hydrogencarbonate. Moisture, usually contained as high as 8−17% in flue gases, badly affects the capacity of conventional adsorbents such as zeolites, but the present technology has no concern with moisture; water is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
144
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(152 citation statements)
references
References 7 publications
6
144
0
Order By: Relevance
“…Al 2 O 3 impregnated with calcined K 2 CO 3 (K 2 CO 3 /Al 2 O 3 ) in particular, appeared to have large surface area, high attrition strength and high mechanical strength Chen et al 2012;Zhao et al 2013). Alkali metal-based adsorbents used chemisorption to capture CO 2 therefore effort is needed for regeneration (Hayashi et al 1998). For regeneration, adsorbent with captured CO 2 is transported to calcination chamber where at moderate temperature of 120-210°C the bicarbonate decomposes and releases CO 2 /H 2 O mixture.…”
Section: Dry Alkali Metal-based Sorbentsmentioning
confidence: 99%
“…Al 2 O 3 impregnated with calcined K 2 CO 3 (K 2 CO 3 /Al 2 O 3 ) in particular, appeared to have large surface area, high attrition strength and high mechanical strength Chen et al 2012;Zhao et al 2013). Alkali metal-based adsorbents used chemisorption to capture CO 2 therefore effort is needed for regeneration (Hayashi et al 1998). For regeneration, adsorbent with captured CO 2 is transported to calcination chamber where at moderate temperature of 120-210°C the bicarbonate decomposes and releases CO 2 /H 2 O mixture.…”
Section: Dry Alkali Metal-based Sorbentsmentioning
confidence: 99%
“…Therefore, a new adsorbent which preferably adsorbs CO2 in the presence of water vapor is required to develop a simple and energy-efficient process by elimination of the dehumidification process. Hydrated potassium carbonate supported on active carbon can absorb CO2 from gas containing water vapor 4) . Solid sorbents in which amines are supported on high surface area supports are also promising as sorbents for CO2 separation 5), 6) .…”
Section: Introductionmentioning
confidence: 99%
“…However, when CO 2 reacts with Na 2 CO 3 , the rate of global carbonation is rather slow (Zhao et al 2009). The CO 2 adsorption and regeneration using potassium-based sorbents with several supports such as activated carbon (Hirano et al 1995;Hayashi et al 1998;Shigemoto et al 2006), TiO 2 , SiO 2 , MgO, ZrO 2 , CaO and Al 2 O 3 were also reported in previous studies (Okunev et al 2000(Okunev et al , 2003Lee et al 2004;Liang et al 2004). Al 2 O 3 is one of the ideal materials used as a sorbent support.…”
Section: Introductionmentioning
confidence: 53%